Captain Cook's Journal During His First Voyage Round the World : Made in H. M. Bark "Endeavour", 1768-71 - Cook, James, 1728-1779; Wharton, W. J. L. (William James Lloyd), 1843-1905 (Salt Lake City, UT : Project Gutenberg, 2005)
"Captain Cook's Journal During His First Voyage Round the World" by James Cook is a historical account written in the late 19th century. The work features a literal transcription of Cook's original manuscripts that detail his significant first voyage aboard H.M. Bark "Endeavour," highlighting his explorations and discoveries across the Pacific, including encounters with new lands and peoples. The opening portion of the book sets the stage for understanding the importance of Cook's narrative, explaining how his journal offers a firsthand look at one of the most celebrated voyages of exploration in history. It describes the excitement of the time and the expectations of scientific discovery, as well as the challenges Cook and his crew faced. The introduction details the genesis of the journal's publication, discussing prior misrepresentations in formal accounts of the voyage and emphasizing the need for an authentic recounting from Cook's own perspective. It lays a foundation for the reader to appreciate the unique insights and experiences Cook documented throughout the journey. (This is an automatically generated summary.)
Release date is 2005-05-01
Produced by Sue Asscher and Col Choat
Keywords: Voyages around the world -- Early works to 1800; Oceania -- Discovery and exploration -- Early works to 1800